The Administrative-Law Consequences of Fraudulent Diplomas in the Appointment of Civil Servant Candidates in Indonesia - Mahalidia, Jihan Virgia; Parsa, I Wayan (International Journal of Business, Law, and Education, 2026)
This article examines the administrative-law implications of using fraudulent diploma documents in the appointment of Civil Servant Candidates (Calon Pegawai Negeri Sipil, CPNS) in Indonesia. The central problem is not merely whether the diploma is false, but whether a State Administrative Decision (Keputusan Tata Usaha Negara, KTUN) appointing a CPNS remains valid when it was issued on the basis of educational credentials that later prove unlawful. Using normative legal research, the article applies statutory and conceptual approaches to Indonesian civil-service law, government-administration law, and doctrinal principles of administrative validity. The analysis demonstrates that a diploma in CPNS recruitment functions as a substantive requirement for proving educational qualification under the merit system, rather than as a purely formal administrative attachment. A fraudulent diploma therefore contaminates the factual basis of the appointment decision and creates a substantive defect in the decision-making process. Nevertheless, under the principle of presumptio iustae causa, the appointment decision remains effective until it is revoked or annulled by the competent authority or by a court. The Personnel Supervisory Officer (Pejabat Pembina Kepegawaian, PPK) may consequently correct the defective decision through revocation (intrekking) or annulment (vernietiging), subject to legality, carefulness, due process, and reasoned decision-making. The article further argues that administrative sanctions, including dishonourable dismissal where the legal requirements are satisfied, may be imposed independently of criminal forgery proceedings. The study contributes to administrative-law scholarship by clarifying the relationship between credential fraud, substantive defects, and the legal continuity of public-employment appointment decisions.